2020
DOI: 10.2147/ijnrd.s243210
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Evocalcet Evaluated by Dialysate Calcium Concentration in Patients with Secondary Hyperparathyroidism Undergoing Hemodialysis</p>

Abstract: Purpose: Evocalcet is a novel oral calcimimetic drug that has demonstrated similar efficacy to cinacalcet in regulating serum parathyroid hormone (PTH), calcium, and phosphate levels, with fewer upper gastrointestinal tract-related adverse drug reactions (ADRs) in patients with secondary hyperparathyroidism undergoing hemodialysis in Japan. We investigated the efficacy and safety of once-daily oral evocalcet under different dialysate calcium concentrations. Patients and Methods: A post hoc analysis by dialysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Most of the dialysis units followed the JSDT guideline published in 2008 [ 25 ] and updated in 2013 accordingly [ 26 ]. Both cinacalcet and evocalcet are effective for controlling secondary hyperparathyroidism [ 27 ] irrespective of D-Ca [ 28 , 29 ]. By comparing the effects on serum calcification propensity (T50), a surrogate marker of calcification, Shoji T et al reported that a calcimimetic agent etelcalcetide was more effective than a vitamin D receptor activator maxacalcitol [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the dialysis units followed the JSDT guideline published in 2008 [ 25 ] and updated in 2013 accordingly [ 26 ]. Both cinacalcet and evocalcet are effective for controlling secondary hyperparathyroidism [ 27 ] irrespective of D-Ca [ 28 , 29 ]. By comparing the effects on serum calcification propensity (T50), a surrogate marker of calcification, Shoji T et al reported that a calcimimetic agent etelcalcetide was more effective than a vitamin D receptor activator maxacalcitol [ 30 ].…”
Section: Discussionmentioning
confidence: 99%